A BIM-based framework for outdoor circulation rule checking - M. Abdelmohsen, Sherif (Universidad de Chile. Facultad de Arquitectura y Urbanismo, 2014)
This paper introduces a BIM-based framework for outdoor circulation rule checking from a geometric modeling perspective. The paper extracts rules and patterns of circulation and interaction based on site planning standards and codes. It then identifies high-level operators and 3D low-level operations involved in applicable circulation rules, and suggest methods for implementation. Mechanisms of integration between high-level operators and low-level operations are defined for different domains of rule checking, based on three types of datasets: 1) BIM objects in outdoor settings, including agents like pedestrians, bikes, vehicles, and other objects; 2) attributes and behavior of objects, and 3) interrelations among objects, including agent-agent or agent-object intersection conflicts, agent-agent or agent-object visual access, unobstructed access, and outdoor lighting and shading.